A study of HLA‐B*15:02 in 9 different Chinese ethnics: Implications for carbamazepine related SJS/TEN. (15th February 2017) - Ou, G. J.; Wang, J.; Ji, X.; Yu, H.; Jiang, L.; Li, L.; Chen, Q.; Su, P. C.; Liu, Z.
Abstract : Background: HLA‐B*15:02 is a known biomarker for carbamazepine (CBZ)‐induced Stevens‐Johnson syndrome and toxic epidermal necrolysis (SJS/TEN) in some ethnic populations. The US FDA recommends B*15:02 screening for Asian and other populations with a high prevalence of B*15:02 prior to treatment with CBZ to prevent drug‐related SJS/TEN. Materials and Methods: A total of 1607 blood samples were collected from volunteer blood donors who were ethnic minorities living in the Yunnan province of southwestern China, including 153 Yi, 193 Naxi, 167 Miao, 156 Lisu, 166 Derung, 211 Bai, 184 Hani, 198 Dai, and 179 Zhuang. The genetic diversity of the HLA‐B*15:02 genes in the ethnic minority samples was examined using sequence based typing at high resolution. Results: The allele frequencies of HLA‐B*15:02 in the Yi, Naxi, Miao, Lisu, Derung, Bai, Hani, Dai, and Zhuang populations were 4.25%, 4.4%, 5.09%, 5.77%, 6.33%, 7.82%, 8.15%, 9.6%, and 15.36%, respectively. The frequencies of HLA‐B*15:02 carriers in the Yi, Naxi, Miao, Lisu, Derung, Bai, Hani, Dai, and Zhuang populations were 8.5%, 8.8%, 9.58%, 10.9%, 12.65%, 15.64%, 16.3%, 18.69%, and 28.49%, respectively. Conclusion: The HLA‐B*15:02 allele frequencies indicated that the prevalence of B*15:02 was different among the different ethnic populations. Because the number of carriers of B*15:02 was high in some ethnic populations, larger studies are required to confirm these findings. The Zhuang population had the highest frequency of B*15:02 in this study. More attention should be paid to CBZ‐induced SJS/TEN in Chinese minority populations.